A systematic review of randomized controlled trials on efficacy and safety of transcranial direct current stimulation in major neurodevelopmental disorders: ADHD, autism, and dyslexia - Mohammad Ali Salehinejad; Elham Ghanavati; Benedikt Glinski; Amir‐Homayun Hallajian; Anita Azarkolah (Brain and Behavior, 2022)
Abstract Objective Among the target groups in child and adolescent psychiatry, transcranial direct current stimulation (tDCS) has been more applied in neurodevelopmental disorders specifically, attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and dyslexia. This systematic review aims to provide the latest update on published randomized‐controlled trials applying tDCS in these disorders for evaluating its efficacy and safety. Methods Based on a pre‐registered protocol (PROSPERO: CRD42022321430) and using the PRISMA approach, a literature search identified 35 randomized controlled trials investigating the effects of tDCS on children and adolescents with ADHD (n = 17), ASD (n = 11), and dyslexia (n = 7). Results In ADHD, prefrontal anodal tDCS is reported more effective compared to stimulation of the right inferior frontal gyrus. Similarly in ASD, prefrontal anodal tDCS was found effective for improving behavioral problems. In dyslexia, stimulating temporoparietal regions was the most common and effective protocol. In ASD and dyslexia, all tDCS studies found an improvement in at least one of the outcome variables while 64.7% of studies (11 of 17) in ADHD found a similar effect. About 88% of all tDCS studies with a multi‐session design in 3 disorders (16 of 18) reported a significant improvement in one or all outcome variables after the intervention. Randomized, double‐blind, controlled trials consisted of around 70.5%, 36.3%, and 57.1% of tDCS studies in ADHD, ASD, and dyslexia, respectively. tDCS was found safe with no reported serious side effects in 6587 sessions conducted on 745 children and adolescents across 35 studies. Conclusion tDCS was found safe and partially effective. For evaluation of clinical utility, larger randomized controlled trials with a double‐blind design and follow‐up measurements are required. Titration studies that systematically evaluate different stimulation intensities, duration, and electrode placement are lacking.